Survey on the working, training, and research conditions of resident physicians in internistic and rheumatological continuing education - BEWUSST - Proft, Fabian; Vossen, Diana; Baraliakos, Xenofon; Berliner, Michael N.; Fleck, Martin; Keyßer, Gernot; Krause, Andreas; Lorenz, Hanns-Martin; Manger, Bernhard; Schuch, Florian; Specker, Christof; Wollenhaupt, Jürgen; et al. (Zeitschrift für Rheumatologie, 2024)
Background: Data on the training and continuing education situation of residents in the field of internal medicine and rheumatology are not available for Germany. For this reason, the Commission for Education and Training of the German Society of Rheumatology (DGRh) initiated the BEWUSST survey on the working, training and research conditions of residents in rheumatology. Methods: A total of 102 questions on the topics of working conditions in everyday professional life, continuing medical education and training, compatibility of career and family, compatibility of work and research, perspectives as a rheumatologist and practical activities were included in an online questionnaire. Results: A total of 102 participants took part in the survey. Of the respondents 48.1% were satisfied with their professional situation, 40.2% of the participants were supervised by a specialist mentor and 54.9% were working as scientists during their work as a physician. A compatibility of family and career was possible for 34.7%. After completion of the residency 52.9% of the respondents aspired to a combined clinical and outpatient activity. Conclusion: Half of the trainee rheumatologists are satisfied with their professional activities, although mentoring of the assistants in training should be further improved. With respect to the desired combined clinical and outpatient activity, the existing options should be expanded or new professional fields of activity should be established, so that the specialty remains attractive for the upcoming generations.
Online veröffentlicht: 17. OKtober 2023